Natural Resources, Tradable and Non-tradable Sector: An Exemplification with Bolivia, a Boom - Tradable and Non-tradable Model - Rivero, Roger Alejandro Banegas; RamÃrez, Marco Alberto Núñez; Caba, Luis Fernando Escobar (International Journal of Energy Economics and Policy, 2017)
In this document the transmission channel between natural resource dependence and its dynamic effects on growth is evaluated (Dutch disease hypothesis). An exemplification is done through a small open economy (Bolivia case) according to representative characteristics of high concentration in exports of hydrocarbon and minerals, and their implications in the productive sectors: boom (B), tradable (T), and non-tradable (NT) [Boom TNT model], plus the addition of domestic demand and relative prices (foreign and domestic) in alternative econometric specifications by structural restrictions (SVAR) for quarterly period from 2000 to 2015. The results show statistical predominance of long-term responses over short-term specifications, and different magnitudes between positive and negative shocks. Keywords: Dutch disease, Growth, Resource booms, Dependence, Tradable, Non-tradable. JEL Classifications: O13, Q33, O41.